2022
DOI: 10.1111/nan.12837
|View full text |Cite
|
Sign up to set email alerts
|

A gene dosage‐dependent effect unveils NBS1 as both a haploinsufficient tumour suppressor and an essential gene for SHH‐medulloblastoma

Abstract: Aims Inherited or somatic mutations in the MRE11, RAD50 and NBN genes increase the incidence of tumours, including medulloblastoma (MB). On the other hand, MRE11, RAD50 and NBS1 protein components of the MRN complex are often overexpressed and sometimes essential in cancer. In order to solve the apparent conundrum about the oncosuppressive or oncopromoting role of the MRN complex, we explored the functions of NBS1 in an MB‐prone animal model. Materials and methods We generated and analysed the monoallelic or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…It was demonstrated that, independently of the DDR, NBS1 deletion up-regulates the NICD protein level, as well as NOTCH activity in neurons, causing in turn repression of neurite outgrowth and neuronal migration in post-mitotic neurons [118]. Moreover, in line with Cheung et al's study which found NOTCH pathway upregulation in lymphoblastoid cell lines from NBS heterozygous carriers [119], we recently published that Nbn heterozygosity increases the Notch pathway and a Notch-dependent clonogenicity in cerebellar granule cell progenitor (cGCPs) primary cultures, isolated from a Medulloblastoma (MB)-prone mouse model [120].…”
Section: Mrn Complex and Cancer-related Pathwaysmentioning
confidence: 69%
See 3 more Smart Citations
“…It was demonstrated that, independently of the DDR, NBS1 deletion up-regulates the NICD protein level, as well as NOTCH activity in neurons, causing in turn repression of neurite outgrowth and neuronal migration in post-mitotic neurons [118]. Moreover, in line with Cheung et al's study which found NOTCH pathway upregulation in lymphoblastoid cell lines from NBS heterozygous carriers [119], we recently published that Nbn heterozygosity increases the Notch pathway and a Notch-dependent clonogenicity in cerebellar granule cell progenitor (cGCPs) primary cultures, isolated from a Medulloblastoma (MB)-prone mouse model [120].…”
Section: Mrn Complex and Cancer-related Pathwaysmentioning
confidence: 69%
“…Collectively our data and those found in the literature converge to the concept that MRN low levels or truncating or missense mutations in MRN genes may play an oncopromoting role as much as the overexpression of functional MRN proteins. Notably, they also reveal that a single wild-type allele (in hemizygous condition) may be sufficient to produce high levels of protein in full-blown tumors [120]. Moreover, in principle, a mutated allele may also be overexpressed.…”
Section: Future Perspective/conclusionmentioning
confidence: 97%
See 2 more Smart Citations
“…MRN complex has the function of inhibiting and promoting tumor growth. Mre11, Rad50, NBS1 and other protein components in the MRN complex are often highly expressed, which is very important for the occurrence and development of tumors [55]. SBB1 existed at the site of DNA double-strand break in the early stage after DNA injury and could combine with MRN complex, suggesting that it was involved in the initial process of DNA double-strand break [56].…”
Section: Discussionmentioning
confidence: 99%